Between escalation and détente: Greek-Turkish relations in the aftermath of the Eastern Mediterranean crisis. (20th October 2022) - Grigoriadis, Ioannis N.
ABSTRACT: This paper aims to evaluate the state of Greek-Turkish relations in light of recent developments in the reconfiguration of Turkish foreign policy. Following twenty years of détente and relative calm in bilateral relations, the year 2020 witnessed two escalations in Greek-Turkish relations, one in March involving refugees and immigrants on the Greek-Turkish land border and another in August involving military vessels of the two countries. The refugee crisis and potential military conflict regarding energy exploration in the Eastern Mediterranean have raised tensions at a moment the political and institutional tools for the promotion of conflict resolution between Greece and Turkey linked to Turkey's EU membership perspective appear to be obsolete. This paper seeks an answer to the question of whether structural or ideational factors played the most prominent role in the recent escalation of the Greek-Turkish disputes.